2021
DOI: 10.1039/d1mh01121a
|View full text |Cite
|
Sign up to set email alerts
|

Red-to-NIR emissive radical cations derived from simple pyrroles

Abstract: Red-to-near-infrared (NIR) fluorophores are highly desirable in bio-imaging study with advantages of high tissue penetration ability and less interference from auto-fluorescence. However, their preparation usually requires tedious synthetic procedures, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…They have been widely investigated and found to have versatile applications in the fields of organic synthesis, 1–4 photoelectronic devices, 5,6 and biotechnology. 7–9 Extensive attempts have been made to investigate the photophysical properties of these sensitive radicals. For example, there are many examples for nitrogen-containing photochromic systems, such as hexaarylbiimidazole derivatives, 10 2,4,6-tri(4-pyridyl)-1,3,5-triazine, 11 phenothiazine-poly(dimethylsiloxane) hybrids, 12 tri- p -tolylamine, 13–15 etc.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely investigated and found to have versatile applications in the fields of organic synthesis, 1–4 photoelectronic devices, 5,6 and biotechnology. 7–9 Extensive attempts have been made to investigate the photophysical properties of these sensitive radicals. For example, there are many examples for nitrogen-containing photochromic systems, such as hexaarylbiimidazole derivatives, 10 2,4,6-tri(4-pyridyl)-1,3,5-triazine, 11 phenothiazine-poly(dimethylsiloxane) hybrids, 12 tri- p -tolylamine, 13–15 etc.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1D, TPA‐DHPy‐Py exhibited the lowest oxidation potential ( E ox = +0.486 V versus Fc/Fc + ) compared to those of TPA‐DHPy, TPA‐DHPy‐NT, TPA‐BTT‐DHPy, and TPA‐BTP‐DHPy ( E ox = +0.529–0.613 V versus Fc/Fc + ), revealing that TPA‐DHPy‐Py can more easily undergo oxidation reactions (Figure S34, Supporting Information). [ 23 ] The oxidative dehydrogenation transformation was further assessed using methylene blue (MB) as a photocatalyst in photoredox reactions due to high singlet oxygen ( 1 O 2 ) generation ability. [ 24 ] With 10 µ m MB and 660 nm laser, the TPA‐Py‐Py generated via oxidative dehydrogenation of TPA‐DHPy‐Py reached a higher yield (59.2%) than that of TPA‐Py (21.5%) upon laser irradiation for 5 min (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that the 2,5‐dimethyl pyrroles can be directly oxidized into red‐to‐NIR emissive radical cations, but they need to be stabilized by supramolecular host CB[7] in water solution [5] . To facilitate the theranostic applications, it's highly desirable to develop water‐stable radical cations without the assistance of supramolecular hosts.…”
Section: Methodsmentioning
confidence: 99%